Exposure to indoor air pollution and adverse pregnancy outcomes in low and middle-income countries: a systematic review and meta-analysis - Daba, Chala; Asmare, Lakew; Demeke Bayou, Fekade; Arefaynie, Mastewal; Mohammed, Anissa; Tareke, Abiyu Abadi; Keleb, Awoke; Kebede, Natnael; Tsega, Yawkal; Endawkie, Abel; Kebede, Shimels Derso; Mesfin, Kaleab; et al. (Frontiers in Public Health, 2024)
Introduction: Exposure to indoor air pollution such as biomass fuel and particulate matter is a significant cause of adverse pregnancy outcomes. However, there is limited information about the association between indoor air pollution exposure and adverse pregnancy outcomes in low and middle-income countries. Therefore, this meta-analysis aimed to determine the association between indoor air pollution exposure and adverse pregnancy outcomes in low and middle-income countries. Methods: International electronic databases such as PubMed, Science Direct, Global Health, African Journals Online, HINARI, Semantic Scholar, and Google and Google Scholar were used to search for relevant articles. The study was conducted according to the updated Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A random effect model at a 95% confidence interval was used to determine the association between indoor air pollution exposure and adverse pregnancy outcomes using STATA version 14. Funnel plot and Higgs I 2 statistics were used to determine the publication bias and heterogeneity of the included studies, respectively. Results: A total of 30 articles with 2,120,228 study participants were included in this meta-analysis. The pooled association between indoor air pollution exposure and at least one adverse pregnancy outcome was 15.5% (95%CI: 12.6-18.5), with significant heterogeneity (I 2 =100%; p < 0.001). Exposure to indoor air pollution increased the risk of small for gestational age by 23.7% (95%CI: 8.2-39.3) followed by low birth weight (17.7%; 95%CI: 12.9-22.5). Exposure to biomass fuel (OR=1.16; 95%CI: 1.12-1.2), particulate matter (OR=1.28; 95%CI: 1.25-1.31), and kerosene (OR= 1.38; 95%CI: 1.09-1.66) were factors associated with developing at least one adverse pregnancy outcomes. We found that more than one in seven pregnant women exposed to indoor air pollution had at least one adverse pregnancy outcome. Specifically, exposure to particulate matter, biomass fuel, and kerosene were determinant factors for developing at least one adverse pregnancy outcome. Therefore, urgent comprehensive health intervention should be implemented in the area to reduce adverse pregnancy outcomes.